Impact of climate change on wheat grain composition and quality - Zahra, Noreen; Hafeez, Muhammad Bilal; Wahid, Abdul; Al Masruri, Muna Hamed; Ullah, Aman; Siddique, Kadambot H.M.; Farooq, Muhammad (Journal of the science of food and agriculture, 2023)
Wheat grain quality, an important determinant for human nutrition, is often overlooked when improving crop production for stressed environments. Climate change makes this task more difficult by imposing combined stresses. The scenarios relevant to climate change include elevated CO2 concentrations (eCO2) and extreme climatic events such as drought, heat waves, and salinity stresses. However, data on wheat quality in terms of climate change are limited, with no concerted efforts at the global level to provide an equitable and consistent climate risk assessment for wheat grain quality. Climate change induces changes in the quality and composition of wheat grain, a premier staple food crop globally. Climate‐change events, such as eCO2, heat, drought, salinity stress stresses, heat + drought, eCO2 + drought, and eCO2 + heat stresses, alter wheat grain quality in terms of grain weight, nutrient, anti‐nutrient, fiber, and protein content and composition, starch granules, and free amino acid composition. Interestingly, in comparison with other stresses, heat stress and drought stress increase phytate content, which restricts the bioavailability of essential mineral elements. All climatic events, except for eCO2 + heat stress, increase grain gliadin content in different wheat varieties. However, grain quality components depend more on inter‐varietal difference, stress type, and exposure time and intensity. The climatic events show differential regulation of protein and starch accumulation, and mineral metabolism in wheat grains. Rapid climate shifting impairs wheat productivity and causes grain quality to deteriorate by interrupting the allocation of essential nutrients and photoassimilates. © 2022 Society of Chemical Industry.